Towards the Synthesis of Isocoronene - Currie, Iain William (Curtin University, 2018)
The concept of aromaticity and its implications are fundamentally important to a wide range of applied sciences involving organic molecules. Isocoronene is unique among polycyclic aromatic hydrocarbons, classified as a non-benzenoid corannulene. Isocoronene has been used as a model compound for computational studies into aromaticity and may provide the first example of a superaromatic molecule. The thesis describes synthetic strategies and experimental work towards the synthesis of isocoronene.